2022
DOI: 10.1029/2022ja030706
|View full text |Cite
|
Sign up to set email alerts
|

Hemispherically Asymmetric Evolution of Nighttime Ionospheric Equatorial Ionization Anomaly in the American Longitude Sector

Abstract: The Global‐scale Observation of Limb and Disk (GOLD) mission observed distinct post‐sunset, hemispherically asymmetric evolution of the equatorial ionization anomaly between 40° and 50°W on 19 November 2018, with the southern crest shifting poleward but the northern crest remaining in the same latitude region. The Whole Atmosphere Community Climate Model‐eXtended captured this phenomenon. Diagnostic analysis revealed that this asymmetric evolution was due to the hemispheric asymmetry in plasma transport by E ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 50 publications
4
15
0
Order By: Relevance
“…The GOLD Far Ultraviolet imager flies onboard the SES-14 telecommunications satellite, which was launched on 25 January 2018 to the geostationary orbit at 47.5 𝐴𝐴 • W (Eastes et al, 2017). GOLD measures the thermospheric/ionospheric airglow emissions from 134 to 162 nm with a spectral resolution of 0.2 nm during daytime (Eastes et al, 2020) and with a spectral resolution of 0.4 nm at nighttime (Cai et al, 2022a(Cai et al, , 2022bEastes et al, 2019) (Yu et al, 2022). In this study, GOLD observed 𝐴𝐴 Σ O/N 2 in the Northern Hemisphere (NH) with a spatial resolution of 1° × 1° on DOY 110 and 111 are utilized.…”
Section: Gold Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The GOLD Far Ultraviolet imager flies onboard the SES-14 telecommunications satellite, which was launched on 25 January 2018 to the geostationary orbit at 47.5 𝐴𝐴 • W (Eastes et al, 2017). GOLD measures the thermospheric/ionospheric airglow emissions from 134 to 162 nm with a spectral resolution of 0.2 nm during daytime (Eastes et al, 2020) and with a spectral resolution of 0.4 nm at nighttime (Cai et al, 2022a(Cai et al, , 2022bEastes et al, 2019) (Yu et al, 2022). In this study, GOLD observed 𝐴𝐴 Σ O/N 2 in the Northern Hemisphere (NH) with a spatial resolution of 1° × 1° on DOY 110 and 111 are utilized.…”
Section: Gold Datamentioning
confidence: 99%
“…The GOLD Far Ultraviolet imager flies onboard the SES‐14 telecommunications satellite, which was launched on 25 January 2018 to the geostationary orbit at 47.5° ${}^{\circ}$W (Eastes et al., 2017). GOLD measures the thermospheric/ionospheric airglow emissions from 134 to 162 nm with a spectral resolution of 0.2 nm during daytime (Eastes et al., 2020) and with a spectral resolution of 0.4 nm at nighttime (Cai et al., 2022a, 2022b; Eastes et al., 2019). The daytime OI 135.6 nm and N 2 LBH bands (140–150 nm) are utilized to derive normalΣ ${\Sigma}$O/N 2 , of which images are in the same regions between 120° ${}^{\circ}$W and 20° ${}^{\circ}$E, 60° ${}^{\circ}$S and 60° ${}^{\circ}$N from 6:10 to 22:40 UT every day (Yu et al., 2022).…”
Section: Data and Modelmentioning
confidence: 99%
“…It should be noted that the density of O + ions is almost equal to the electron density (Ne) in the ionosphere F2 region. The O + and electron densities in the ionosphere F2 region are determined by the following equation (Cai et al, 2022a(Cai et al, , 2022bJ. Liu, Wang, Burns, Solomon, et al, 2016)…”
Section: Diagnostic Analysis Of Ionosphere F2 Region O + Density In T...mentioning
confidence: 99%
“…It should be noted that the density of O + ions is almost equal to the electron density (Ne) in the ionosphere F2 region. The O + and electron densities in the ionosphere F2 region are determined by the following equation (Cai et al., 2022a, 2022b; J. Liu, Wang, Burns, Solomon, et al., 2016) NO+t=qO+βNO+·()NO+trueV $\frac{\partial {N}_{{O}^{+}}}{\partial t}={q}_{{O}^{+}}-\beta {N}_{{O}^{+}}-\nabla \cdot \left({N}_{{O}^{+}}\stackrel{\rightharpoonup }{V}\right)$ where NO+/t $\partial {N}_{{O}^{+}}/\partial t$ stands for the change rate of the O + density; qO+ ${q}_{{O}^{+}}$ is the chemical production rate; βNO+ $\beta {N}_{{O}^{+}}$ is the loss rate; ·()NO+trueV $\nabla \cdot \left({N}_{{O}^{+}}\stackrel{\rightharpoonup }{V}\right)$ includes plasma transport due to neutral winds, E × B drift, and ambipolar diffusion. For convenience, the O + density change rate ( δO + ) induced by chemical production and loss rates, neutral wind transport, E × B transport, and ambipolar diffusion are termed as δOnormalCnormalhnormalenormalm+ $\delta {O}_{\mathrm{C}\mathrm{h}\mathrm{e}\mathrm{m}}^{+}$, δOnormalWnormalinormalnnormald+ $\delta {O}_{\mathrm{W}\mathrm{i}\mathrm{n}\mathrm{d}}^{+}$, δOnormalE×normalB+ $\delta {O}_{\mathrm{E}\times \mathrm{B}}^{+}$, and δOnormalAnormalmnormalbnormali<...…”
Section: Data and Modelmentioning
confidence: 99%
“…The GOLD instrument is onboard the SES‐14 telecommunications satellite which was launched on 25 January 2018 to geosynchronous orbit at a longitude of 47.5° ${}^{\circ}$W (Eastes et al., 2017). GOLD observes thermospheric/ionospheric Far Ultraviolet airglow emissions on the Earth's limb and disk from 134 to 162 nm with a high spectral resolution of 0.2 nm (Eastes et al., 2017, 2020) during daytime and a spectral resolution of 0.35 nm during nighttime (Cai et al., 2022a, 2022b; Eastes et al., 2019). The observed OI 135.6 nm and LBH bands are inverted to derive daytime normalΣ ${\Sigma}$O/N 2 (Correira et al., 2021; Strickland et al., 1995).…”
Section: Data and Modelmentioning
confidence: 99%